Impact of Nonoptimal Intakes of Saturated, Polyunsaturated, and Trans Fat on Global Burdens of Coronary Heart Disease. Issue 1 (20th January 2016) - Wang, Qianyi; Afshin, Ashkan; Yakoob, Mohammad Yawar; Singh, Gitanjali M.; Rehm, Colin D.; Khatibzadeh, Shahab; Micha, Renata; Shi, Peilin; Mozaffarian, Dariush; ,
Abstract : Background: Saturated fat (SFA), ω‐6 (n‐6) polyunsaturated fat (PUFA), and trans fat (TFA) influence risk of coronary heart disease (CHD), but attributable CHD mortalities by country, age, sex, and time are unclear. Methods and Results: National intakes of SFA, n‐6 PUFA, and TFA were estimated using a Bayesian hierarchical model based on country‐specific dietary surveys; food availability data; and, for TFA, industry reports on fats/oils and packaged foods. Etiologic effects of dietary fats on CHD mortality were derived from meta‐analyses of prospective cohorts and CHD mortality rates from the 2010 Global Burden of Diseases study. Absolute and proportional attributable CHD mortality were computed using a comparative risk assessment framework. In 2010, nonoptimal intakes of n‐6 PUFA, SFA, and TFA were estimated to result in 711 800 (95% uncertainty interval [UI] 680 700–745 000), 250 900 (95% UI 236 900–265 800), and 537 200 (95% UI 517 600–557 000) CHD deaths per year worldwide, accounting for 10.3% (95% UI 9.9%–10.6%), 3.6%, (95% UI 3.5%–3.6%) and 7.7% (95% UI 7.6%–7.9%) of global CHD mortality. Tropical oil–consuming countries were estimated to have the highest proportional n‐6 PUFA– and SFA‐attributable CHD mortality, whereas Egypt, Pakistan, and Canada were estimated to have the highest proportional TFA‐attributable CHD mortality. From 1990 to 2010 globally, the estimated proportional CHD mortality decreased by 9% for insufficient n‐6 PUFA and by 21% for higher SFA, whereas it increased by 4% for higher TFA, with the latter driven by increases in low‐ and middle‐income countries. Conclusions: Nonoptimal intakes of n‐6 PUFA, TFA, and SFA each contribute to significant estimated CHD mortality, with important heterogeneity across countries that informs nation‐specific clinical, public health, and policy priorities.